Strength performance of sustainable mortar containing recycle sewage sludge ash (SSA) / Nurul Nazierah Mohd Yusri … [et al.] - Mohd Yusri, Nurul Nazierah; Kamaruddin, Kartini; Mohd Saman, Hamidah; Tutur, Nuraini (Institute of Research Management and Innovation (IRMI), 2018)
Sewage sludge is a by-product generated within the wastewater treatment process. Severe concern arised as the sludge are massively been dumped to the landfill and it may affect the environment. Many studies had been conducted in reusing the sewage sludge as construction material, where it is one of the optional ways to solve the issue. In this study, dried sewage sludge was incinerated with two different temperatures in order to produce sewage sludge ash (SSA), which are 800°C and 1000°C. After few processes, this SSA then reused in mortar as cement replacement with the replacement percentage of 5%, 10%, 15% and 20% by weight. The strength performance of mortar specimens was investigated after 7, 28, 60 and 90 days of curing. From the results, it is clearly showed that the compressive strength of all mortar specimens increased when the period of curing was prolonged. Moreover, almost all compressive strength of SSA mortars was higher than the control mortar. Therefore, there is potential to reuse this waste material as part of construction materials and hence, its plays an important role for future researches in minimisation of waste.